Evidence for tolerance in psychedelic microdosing from the self-blinding microdose trial - Baumann,S; Carhart-Harris,R; Nutt,D; Erritzoe,D; Szigeti,B (2022)
Microdosing is the practice of regularly using very low doses of psychedelic drugs. Anecdotal reports suggest that it may enhance well-being, creativity and cognition. Here, we use data from a self-blinding microdose trial, a large (n=240) placebo-controlled citizen science trial of microdosing to investigate whether tolerance develops during microdosing. We conceptualized tolerance as the relationship between correct microdose guess probability and the number of previous microdoses taken within the trial’s timeframe: if tolerance develops then, correct microdose guess probability should decrease with more microdoses taken. Mixed linear regression models show that correct microdose guess probability decreases with number of microdoses taken (mean±se: -.017±.007; p=.009), suggesting that tolerance developed. Secondary post-hoc analysis revealed that this tolerance was present with LSD/LSD-analogue microdoses (mean±se: -.026±.007; p<.001), but not with psilocybin microdoses (mean±se: .013±.014; p=.36). These results suggest that microdosers may need to periodically suspend their microdosing routine to avoid tolerance and that psilocybin may be better suited for long-term microdosing protocols.